Magnetic field inhomogeneities due to CO2 incubator shelves: a source of experimental confounding and variability?. Issue 2 (14th February 2018) - Makinistian, L.; Belyaev, I.
Abstract : A thorough assessment of the static magnetic field (SMF) inside a CO2 incubator allowed us to identify non-negligible inhomogeneities close to the floor, ceiling, walls and the door. Given that incubator's shelves are made of a non-magnetic stainless steel alloy, we did not expect any important effect of them on the SMF. Surprisingly, we did find relatively strong distortion of the SMF due to shelves. Indeed, our high-resolution maps of the SMF revealed that distortion is such that field intensities differing by a factor of up to 36 were measured on the surface of the shelf at locations only few millimetres apart from each other. Furthermore, the most intense of these fields was around five times greater than the ones found inside the incubator (without the metallic shelves in), while the lowest one was around 10 times lower, reaching the so-called hypomagnetic field range. Our findings, together with a survey of the literature on biological effects of hypomagnetic fields, soundly support the idea that SMF inhomogeneities inside incubators, especially due to shelves' holes, are a potential source of confounding and variability in experiments with cell cultures kept in an incubator.